2017
DOI: 10.1055/s-0037-1606604
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Symptoms and Associated Risk Factors between Male and Female University Teachers

Abstract: Introduction  Many recent studies on teachers warn of the adverse effects that voice problems have on work performance. However, only a few of these studies included university teachers. Objective  To compare the vocal symptoms and risk factors between male and female university teachers in a private institution within the city of São Paulo. Methods  In a cross-sectional survey, a voice self-evaluation form prepared by the Ministry of Labor in Brazil was administered to 846 university teachers at a private i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…In addition there are structural gender differences in the anatomy of the larynx. Women have shorter vocal folds than men (so that the fundamental frequency of speaking is higher), (Hunter et al 2011), (Korn et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition there are structural gender differences in the anatomy of the larynx. Women have shorter vocal folds than men (so that the fundamental frequency of speaking is higher), (Hunter et al 2011), (Korn et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…La gran limitante del estudio fue que solo se evaluaron bajo visión endoscópica 28 profesores de 53 que presentaron incapacidad moderada y severa, porque estos fueron los únicos que decidieron continuar con el estudio endoscópico de la laringe [13][14][15][16] . En este punto vale la pena precisar que existen dispositivos para diagnósticos endoscópicos más precisos, como la laringoestroboscopia, de los cuales carece la ciudad origen del estudio y que serían motivo de otra investigación.…”
Section: Discussionunclassified
“…The frequent occurrence of vocal symptoms or complaints in professors impairs performance and contributes to the idea of the future profession changing due to vocal problems (11,12). Studies show that the voice problems of university professors should be studied in a separate group (4,13). A 2017 study by Ahmed et al reported an abnormal voice in 38.8% of participants in a population of university professors (14).…”
Section: Introductionmentioning
confidence: 99%